Antihypertensive treatment in people with dementia - van der Wardt, Veronika; Logan, Phillipa A.; Conroy, Simon; Harwood, Rowan H.; Gladman, John R.F. (Elsevier, 2014)
Introduction The range and magnitude of potential benefits and harms of antihypertensive treatment in people with dementia has not been previously established. Method A scoping review to identify potential domains of benefits and harms of antihypertensive therapy in people with dementia was undertaken. Systematic reviews of these domains were undertaken to examine the magnitude of the benefits or harms. Results Potential outcome domains identified in the 155 papers in the scoping review were cardio-vascular events, falls, fractures and syncope, depression, orthostatic hypotension, behavioural disturbances, polypharmacy risks, kidney problems, sleep problems, interactions with cholinesterase inhibitors and pain. The systematic reviews across these domains identified relatively few studies done in people with dementia, and no convincing evidence of safety, benefit or harm across any of them. Discussion There is no justification for materially different guidance for the treatment of hypertension in people with dementia, but sufficient evidence to warrant particular caution and further research into treatment in this group of patients.